Drug design from the cryptic inhibitor envelope - Chul-Jin Lee (Nature Portfolio, 2016)
The conformational dynamics of a compound has a large effect on ligand/receptor binding. Here, the authors employ NMR spectroscopy to study ligand binding to the enzyme LpxC, discovering an inhibitor envelope that was not identifiable by crystallography and subsequently developing a highly potent inhibitor.